Covariation Between Microbiome Composition and Host Transcriptome in the Gut of Wild Drosophila melanogaster: A Re‐Analysis - Frances Llanwarne; Adam J. Dobson (Ecology and Evolution)
ABSTRACT Gut microbiota are fundamental for healthy animal function, but the evidence that host function can be predicted from microbiota taxonomy remains equivocal, and natural populations remain understudied compared to laboratory animals. Paired analyses of covariation in microbiota and host parameters are powerful approaches to characterise host–microbiome relationships mechanistically, especially in wild populations of animals that are also lab models, enabling insight into the ecological basis of host function at molecular and cellular levels. The fruitfly Drosophila melanogaster is a preeminent model organism, amenable to field investigation by ‘omic analyses. Previous work in wild male D. melanogaster guts analysed paired measurements of (A) bacterial diversity and abundance, measured by 16S amplicon sequencing; and (B) the host gut transcriptome, but no signature of covariation was detected. Here, we re‐analyse those data comprehensively. We find orthogonal axes of microbial genera, which correspond to differential expression of host genes. The differentially expressed gene sets were enriched in functions including protein translation, mitochondrial respiration, immunity and reproduction. Each gene set had a distinct functional signature, suggesting that wild flies exhibit a range of distinct axes of functional variation, which correspond to orthogonal axes of microbiome variation. These findings lay a foundation to better connect ecology and functional genetics of a leading host‐microbiome model.